Art coating with formaldehyde removal and antibacterial functions and preparation method thereof
By constructing a dispersion-solubilizing and delayed crosslinking system, the problem of early crosslinking between active zinc-containing components and anionic polymer groups was solved, improving the application stability of the coating and the mechanical properties of the coating film, and achieving long-lasting formaldehyde removal and antibacterial effects.
Patent Information
- Application Number
- CN202611424571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-11-06
AI Technical Summary
Existing coatings with formaldehyde removal and antibacterial functions are prone to unplanned cross-linking reactions with anionic polymer groups when active zinc-containing components are introduced, leading to coating flocculation, demulsification, and gelation, affecting the application performance. Furthermore, the coating film is prone to cracking when drying in thick coats, and functional substances are easily lost after washing, resulting in performance degradation.
A dispersion, solubilization, and delayed crosslinking system was constructed using components such as propylene glycol, isotridecyl alcohol polyoxyethylene ether, acetylacetone, and ammonia. Through steric hindrance and ligand complexation, early crosslinking was inhibited, forming a coordination crosslinking network of acetylated polyvinyl alcohol and active zinc. Combined with inorganic powder gradation filling, the strength and stability of the coating film were improved.
Maintaining the stability of the coating liquid phase reduces the risk of coating film cracking, improves the mechanical washability and long-lasting antibacterial and formaldehyde removal efficacy of the coating film, and ensures that functional substances can maintain good performance after multiple water washes.
Smart Images

Figure CN123042575A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to an artistic coating with formaldehyde removal and antibacterial functions and its preparation method. Background Technology
[0002] As people's demands for healthy living environments increase, environmentally friendly interior wall art coatings with formaldehyde removal and antibacterial functions are gradually becoming the mainstream in the market. To achieve these functions, zinc-containing species with catalytic degradation and antibacterial activities, such as active zinc oxide, are usually introduced into the formula. At the same time, to meet the application texture and basic physical property requirements of art coatings, the system often uses water-based anionic polymer emulsions as the main film-forming base material.
[0003] However, directly incorporating highly reactive zinc-containing species into aqueous anionic emulsion systems can easily lead to liquid phase stability issues. Free zinc ions spontaneously undergo strong association and ionic cross-linking reactions with anionic groups such as carboxyl groups on polymer molecular chains. This unplanned early cross-linking often occurs during the coating's production mixing stage or in-tank storage, resulting in localized aggregation, flocculation, or even overall gelation of the system. This disrupts the emulsion's microscopic stability, causing the coating to lose its normal flowability and application properties, and in severe cases, can easily lead to demulsification.
[0004] Furthermore, because conventional water-based coatings evaporate moisture quickly during thick application, the stress generated by internal volume shrinkage can easily lead to cracking defects in the dry film if it is not effectively released. Moreover, in the cured coating film, the functional zinc-containing substances and some water-soluble additives often lack effective chemical anchoring and are only physically dispersed in the resin matrix. When the wall coating is subjected to scrubbing or exposed to high humidity environments during daily use, these free components are prone to swelling and leaching outwards, causing an increase in surface roughness and a short-term decline in its formaldehyde removal and antibacterial functions. Summary of the Invention
[0005] The technical problem solved by this invention is that: when existing coatings with formaldehyde removal and antibacterial functions introduce active zinc-containing components into the formulation, these zinc-containing species often easily undergo unplanned cross-linking reactions with anionic polymer groups inside the system.
[0006] This situation often occurs during the preparation or liquid phase storage stage, and may cause coating flocculation, demulsification, or even gelation, thereby affecting normal construction operations.
[0007] In addition, when this type of coating is applied in thick layers and dried, it is prone to cracking due to volume shrinkage stress.
[0008] Furthermore, since functional substances lack effective structural fixation in conventional systems, the formaldehyde removal and antibacterial effects of the coating usually show varying degrees of attenuation after repeated washing.
[0009] To address the above problems, the present invention provides the following technical solution:
[0010] In a first aspect, the present invention provides an art paint with formaldehyde removal and antibacterial function, which adopts the following technical solution: an art paint with formaldehyde removal and antibacterial function, made from raw materials containing the following parts by weight: deionized water: 15.0 to 25.0 parts;
[0011] Propylene glycol: 1.5–3.0 parts;
[0012] Isomeric tridecyl alcohol polyoxyethylene ether: 0.2–0.6 parts;
[0013] Sodium polyacrylate aqueous solution: 0.5–1.0 parts;
[0014] Active zinc oxide: 1.0–3.0 parts;
[0015] Acetylacetone: 0.5–1.5 parts;
[0016] Ammonia solution: 1.0–2.5 parts;
[0017] Aqueous acetylated polyvinyl alcohol aqueous solution: 10.0–15.0 parts;
[0018] Pigments and fillers: 30.0–45.0 parts;
[0019] Anionic styrene-acrylic emulsion: 30.0–40.0 parts;
[0020] Polyether-modified siloxane defoamer: 0.2–0.5 parts;
[0021] Hydrophobic modified polyurethane associative thickener: 0.3-0.8 parts.
[0022] By adopting the above technical solution, the present invention constructs a system at the formulation level that includes dispersion solubilization, ligand complexation and delayed crosslinking, which to a certain extent helps to maintain the stability of the coating in the liquid phase and improve the strength of the cured coating film.
[0023] Specifically, propylene glycol and isotridecyl alcohol polyoxyethylene ether work synergistically in an aqueous environment to provide a dispersion medium for zinc oxide particles. The steric hindrance effect inhibits the micro-aggregation of zinc-containing particles, resulting in a relatively narrow particle size distribution within the system, which facilitates subsequent reactions.
[0024] Based on this, the added acetylacetone and ammonia water act as ligands, which complex with the active zinc-containing species and occupy part of the coordination orbitals of the zinc atom.
[0025] This passivation treatment reduces the direct association between free zinc ions and free carboxyl groups in anionic styrene-acrylic emulsions, which helps the coating maintain relatively stable flowability and viscosity during storage.
[0026] During the film-forming stage after construction, as moisture and some volatile ammonia are released, the active sites of zinc-containing species gradually become visible. At this time, the acetylacetyl groups on the acetylated polyvinyl alcohol chain segments chelate with it.
[0027] Because the construction of this cross-linked network is relatively delayed, the fluid state maintained by the coating in the early stage of film formation can provide a certain stress relaxation time for volume shrinkage, reducing the probability of cracking of thick coatings.
[0028] The polymer-metal coordination crosslinking structure that gradually forms in the later stages of film formation fixes the originally easily soluble polymer segments and zinc-containing substances relatively within the system, thereby better maintaining the smoothness of the coating after mechanical washing and its long-lasting antibacterial and formaldehyde removal effects.
[0029] Preferably, the pigment and filler are composed of rutile titanium dioxide, heavy calcium carbonate and talc, and the weight ratio of rutile titanium dioxide, heavy calcium carbonate and talc is 10.0 to 15.0 to 15.0 to 20.0 to 5.0 to 10.0.
[0030] By adopting the above technical solutions, these inorganic powders differ in morphology and particle size, and can produce a certain gradation filling effect inside the coating film.
[0031] Rutile titanium dioxide mainly serves a masking function, while heavy calcium carbonate and talc participate in building the coating skeleton.
[0032] This inorganic filler system, combined with the polymer crosslinking network, can increase the tortuosity of external moisture penetration to a certain extent, thereby positively affecting the washability of the dry film.
[0033] Preferably, the average number of ethylene oxide additions in the isomeric tridecyl alcohol polyoxyethylene ether is 6;
[0034] The active zinc oxide is a powder with a purity of ≥99.7wt% and an average particle size D50 of 0.8μm;
[0035] The anionic styrene-acrylic emulsion is a high-molecular-weight aqueous dispersion copolymerized from styrene, butyl acrylate and carboxyl-containing unsaturated monomers, with a solid content of 48 wt% and a pH value of 7.5 to 8.0.
[0036] By adopting the above technical solution, nonionic surfactants with a specific addition number have matching hydrophilicity and lipophilicity, and are more likely to form a stable interfacial film with the solvent.
[0037] High-purity active zinc oxide with finer particle size has a relatively sufficient specific surface area, which helps it to participate more fully in the complexation reaction during the bottom liquid stage.
[0038] Choosing a weakly alkaline carboxylated styrene-acrylic emulsion not only maintains its own colloidal repulsion stability, but also provides better compatibility with the slightly alkaline base solution after complexation treatment, reducing the risk of demulsification caused by excessive pH differences.
[0039] Preferably, the acetylated polyvinyl alcohol aqueous solution has a solid content of 15.0 ± 0.2 wt%, and is prepared from raw materials comprising the following parts by weight:
[0040] 85.0 parts deionized water, 15.0 parts partially hydrolyzed polyvinyl alcohol, 0.075 parts anhydrous sodium acetate, and 1.14 to 2.28 parts diketene;
[0041] The method for preparing the acetylated polyvinyl alcohol aqueous solution includes the following steps:
[0042] Heat deionized water to 92°C, add part of the alcoholysis-type polyvinyl alcohol while stirring at a constant speed, and stir at a constant temperature until completely dissolved; cool down to 62°C, add anhydrous sodium acetate and stir evenly.
[0043] Maintain the temperature at 62℃, add diketene dropwise, and control the dropwise addition process to be completed within 1 to 1.5 hours. After the dropwise addition is completed, continue to keep the temperature at 62℃ and stir the reaction for 2 hours.
[0044] After the reaction was completed, the mixture was cooled to room temperature, and deionized water was added to adjust the solid content to 15.0 ± 0.2 wt%.
[0045] By adopting the above technical solution, under weakly alkaline conditions, diketene undergoes ring-opening and an addition reaction with the hydroxyl groups on the polyvinyl alcohol segment to generate an acetyl acetyl side chain.
[0046] Controlling the amount of diketene and the appropriate dripping time aims to regulate the grafting density of polyvinyl alcohol.
[0047] A suitable degree of modification can not only provide coordination sites for network construction, but also help avoid situations such as a sharp increase in the viscosity of aqueous solutions or a brittle final coating due to excessive crosslinking.
[0048] Secondly, the present invention provides a method for preparing an artistic coating with formaldehyde removal and antibacterial functions, employing the following technical solution:
[0049] A method for preparing an artistic coating with formaldehyde removal and antibacterial functions includes the following steps:
[0050] S1. Control the temperature of the material in the reactor to 25 to 35°C, and add deionized water, propylene glycol, isotridecyl alcohol polyoxyethylene ether, sodium polyacrylate aqueous solution and the first part of polyether modified siloxane defoamer in sequence and stir.
[0051] Then, active zinc oxide was added and stirred to disperse the mixture. Acetylacetone was added dropwise while maintaining the stirring speed, followed by the addition of ammonia water. The pH of the system was controlled between 10.2 and 10.5 to form a dispersion base liquid.
[0052] S2. Maintain the temperature inside the reactor, add an acetylated polyvinyl alcohol aqueous solution to the dispersion base liquid, and increase the rotation speed to maintain a constant stirring speed;
[0053] S3. Maintain high-speed shearing state, add pigments and fillers sequentially, continue high-speed dispersion, and control the slurry fineness to be less than or equal to 40μm;
[0054] S4. Reduce the rotation speed and slowly and uniformly add the anionic styrene-acrylic emulsion. After the addition is complete, maintain low-speed stirring.
[0055] S5. Add the second part of polyether-modified siloxane defoamer and hydrophobic-modified polyurethane associative thickener, stir at low speed, let stand to defoam, and then filter to obtain the final product.
[0056] By adopting the above technical solution, the preparation process of the present invention mainly coordinates with the aforementioned physicochemical changes, and reduces the occurrence of side reactions by stepwise feeding.
[0057] Before introducing the polymer emulsion, the S1 step is performed separately to allow the dispersion and complexation passivation of zinc oxide to take place in a relatively independent system, while the pH value is controlled to slow down the volatilization of ammonia ligands.
[0058] After most of the zinc species are in a non-free state, the film-forming polymer is mixed and the pigments and fillers are dispersed, so that the mechanical depolymerization process of the powder occurs in the already passivated and stabilized bottom liquid.
[0059] When introducing the styrene-acrylic emulsion in step S4, the process is adjusted to a low-shear state. This is mainly to avoid the risk of mechanical thermal demulsification caused by high shear. At the same time, by physically isolating the feeding sequence, the probability of early contact between anionic groups and active zinc is reduced as much as possible, thereby providing process assurance for the liquid phase stability of the coating throughout its entire life cycle.
[0060] Preferably, in step S1, after adding deionized water, propylene glycol, isotridecyl alcohol polyoxyethylene ether, sodium polyacrylate aqueous solution and the first part of polyether modified siloxane defoamer in sequence, the mixture is stirred at a speed of 300 to 400 rpm for 10 minutes.
[0061] After adding the active zinc oxide, increase the speed to 800 to 1000 rpm and stir for 10 minutes;
[0062] The weight ratio of the first part of the polyether-modified siloxane defoamer to the second part of the polyether-modified siloxane defoamer is 1:1.
[0063] By adopting the above technical solution, the step-by-step operation from low-speed mixing in the early stage to increasing the speed in the later stage better adapts to the rheological state changes of materials from initial wetting to solid deagglomeration.
[0064] Adding defoamers in batches, the former is mainly used to alleviate the initial foaming after the introduction of surfactants, while the latter is used to treat the tiny bubbles that are dispersed and mixed in at high speed, which helps to improve the overall defoaming effect.
[0065] Preferably, in step S3, the rotation speed during high-speed shearing is 1200 to 1500 rpm, and the high-speed dispersion time is 30 to 60 minutes.
[0066] During high-speed dispersion, the temperature is maintained at 25 to 35°C by controlling the cooling water in the reactor jacket.
[0067] By adopting the above technical solution, suitable strong shear conditions are beneficial to crushing and deagglomerating the slurry to the required fineness, thereby improving the appearance and smoothness of the paint film.
[0068] During this period, jacket cooling is used to control the system temperature, which can alleviate the ammonia gas escape caused by the temperature rise due to mechanical friction, maintain the balance of the complexed state in the bottom liquid as much as possible, and make the process operation more tolerant.
[0069] Preferably, in step S4, the reduced rotational speed is 300 to 400 rpm;
[0070] In step S5, the low-speed stirring speed is 300 to 400 rpm, and the stirring time is 10 minutes.
[0071] By adopting the above technical solution, switching to low-speed stirring in the middle and later stages of feeding aims to reduce the damage of high-intensity shear to the microstructure of polymer emulsion and the thickener association network, so that the final rheological characteristics of the finished product can basically meet the expected settings.
[0072] This invention provides an artistic coating with formaldehyde-removing and antibacterial functions, and its preparation method. It possesses the following beneficial effects:
[0073] 1. This invention utilizes a dual-ligand system formed by acetylacetone and ammonia to complex with active zinc oxide during the independent preparation stage of the base solution, occupying the coordination orbitals of zinc. This passivation treatment reduces the direct contact between free zinc ions and the carboxyl groups in the subsequently added anionic styrene-acrylic emulsion, lowering the risk of unplanned flocculation, demulsification, or a sharp increase in viscosity during preparation and storage, thus maintaining the processing stability and application fluidity of the coating in the liquid phase.
[0074] 2. In the coating drying and film-forming stage of this invention, as moisture and volatile ammonia ligands gradually dissipate, a delayed cross-linking reaction occurs in the system, and the acetoacetyl groups on the acetylated polyvinyl alcohol chelate with the gradually reactivating zinc-containing species. This cross-linking network construction process, which lags behind moisture evaporation, provides a buffer time for stress release during coating volume shrinkage under thick coating conditions, thereby reducing the occurrence of surface cracking of the coating.
[0075] 3. This invention utilizes a polymer-metal coordination crosslinking network formed by acetylated polyvinyl alcohol and zinc-containing species during the later stages of film formation. Water-soluble polymer segments and zinc-containing components, which provide formaldehyde removal and antibacterial effects, are relatively fixed within the dry film structure. This network structure restricts the migration and loss of functional substances and some water-soluble components during repeated mechanical washing, allowing the coating to maintain good mechanical smoothness and antibacterial and formaldehyde removal efficacy even after multiple washes. Attached Figure Description
[0076] Figure 1 This is a comparison curve of the particle size distribution of test sample A and test sample B in Test Example 1;
[0077] Figure 2 This is a dynamic evolution diagram of the characteristic infrared absorption peaks during the drying process of the coating in Example 2 of Test Example 2;
[0078] in: Figure 2 (a) is a graph showing the dynamic evolution of the infrared spectrum with drying time; Figure 2 (b) is a graph showing the trend of the relative retention rate of the acetoacetyl main peak and the ammonia characteristic peak with drying time;
[0079] Figure 3 The graph shows the evolution of the storage modulus and loss modulus of the coating in Test Example 3 over time; where:
[0080] Figure 3 (a) is a graph showing the evolution of energy storage modulus (G') and loss modulus (G'') over time in Example 2; Figure 3 (b) is a graph showing the evolution of the energy storage modulus (G') and loss modulus (G'') over time in Comparative Example 1;
[0081] Figure 4 A bar chart comparing the accelerated thermal storage stability test (initial viscosity and viscosity after thermal storage) of the coatings in Example 4 with those in the comparative example.
[0082] Figure 5 This is a comparison chart of the physical and mechanical properties and appearance smoothness of the coatings in the examples and comparative examples in Test Example 5; wherein:
[0083] Figure 5(a) is a comparison chart of the maximum crack resistance thickness of each coating film; Figure 5 (b) is a comparison chart of the surface roughness (Ra) of each coating film;
[0084] Figure 6 This is a comparison chart of the functional degradation data of the coatings in Example 6 and the comparative example during the water washing and aging process.
[0085] in: Figure 6 (a) is a comparison chart of the formaldehyde purification rate of each coating under different water washing cycles; Figure 6 (b) is a comparison chart of the antibacterial rates of each coating under different water washing cycles. Detailed Implementation
[0086] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0087] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0088] Isomerized tridecyl alcohol polyoxyethylene ether, with the molecular formula RO(CH2CH2O). R is isotriadecyl, the average number of ethylene oxide additions n is 6, the purity is ≥99wt%, and the CAS number is 69011-36-5.
[0089] Sodium polyacrylate aqueous solution, with the molecular formula (C3H3NaO2)n, has a solid content of 40wt% and a weight-average molecular weight of [missing information]. It has a concentration of 2500 g / mol, a pH value of 7.0-8.5, and a CAS number of 9003-04-7.
[0090] Polyether-modified siloxane defoamer, with an active ingredient content of 100wt%, is a light yellow transparent liquid in appearance, and its CAS number is 67674-67-3.
[0091] Activated zinc oxide, a powder prepared by an indirect method, has the chemical formula: The purity is ≥99.7wt%, the average particle size D50 is 0.8μm, the specific surface area is 4.5m2 / g, and the CAS number is 1314-13-2.
[0092] Acetylacetone, chemical name 2,4-pentanedione, chemical formula C5H8O2, purity ≥99.5wt%, boiling point 140℃, CAS number 123-54-6.
[0093] Polyvinyl alcohol, specifically partially hydrolyzed polyvinyl alcohol, with a degree of hydrolysis of 88 mol%, an average degree of polymerization of 1700, and a weight-average molecular weight of [missing information]. It is approximately 74,800 g / mol, and its CAS number is 9002-89-5.
[0094] Diketene, chemically known as 4-methylene-2-oxacyclobutanone, has the molecular formula C4H4O2, a purity ≥99.0wt%, and the CAS number 674-82-8.
[0095] An anionic styrene-acrylic emulsion is a high-molecular-weight aqueous dispersion copolymerized from styrene, butyl acrylate, and a small amount of carboxyl-containing unsaturated monomers. The polymer segments contain free carboxyl groups introduced during copolymerization. The solid content is 48 wt%, the pH is 7.5-8.0, and the glass transition temperature is [not specified]. The temperature was 20℃, and the average particle size was 120nm.
[0096] Hydrophobic modified polyurethane associative thickener, nonionic polyurethane rheology modifier, solid content 20wt%, solvent is a mixture of water and propylene glycol.
[0097] Preparation Example 1:
[0098] This preparation example provides a method for preparing an aqueous solution of acetylated polyvinyl alcohol, comprising the following steps:
[0099] Add 85.0 parts by weight of deionized water to the reactor and heat to 92°C. Slowly add 15.0 parts by weight of polyvinyl alcohol while stirring at a constant speed, and stir at a constant temperature for 2.5 hours until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol aqueous solution.
[0100] Cool the polyvinyl alcohol aqueous solution to 62°C, add 0.075 parts by weight of anhydrous sodium acetate, and stir until homogeneous.
[0101] Maintain the temperature at 62°C and slowly add 1.14 parts by weight of diketene to the system, controlling the dropping rate so that the dropping process is completed within 1 hour.
[0102] After the addition is complete, continue to keep the mixture at 62°C with stirring for 2 hours.
[0103] After the reaction was completed, the reactants were cooled to room temperature, the solid content of the system was measured, and deionized water was added to adjust the solid content to 15.0 ± 0.2 wt%. The actual degree of modification of the acetylacetyl group in the obtained polyvinyl alcohol was determined by ¹H NMR to obtain an aqueous solution of acetylated polyvinyl alcohol.
[0104] Preparation Example 2:
[0105] This preparation example provides a method for preparing an aqueous solution of acetylated polyvinyl alcohol, comprising the following steps:
[0106] Add 85.0 parts by weight of deionized water to the reactor and heat to 92°C. Slowly add 15.0 parts by weight of polyvinyl alcohol while stirring at a constant speed, and stir at a constant temperature for 2.5 hours until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol aqueous solution.
[0107] Cool the polyvinyl alcohol aqueous solution to 62°C, add 0.075 parts by weight of anhydrous sodium acetate, and stir until homogeneous.
[0108] Maintain the temperature at 62°C and slowly add 1.71 parts by weight of diketene to the system, controlling the dropping rate to complete the process within 1.2 hours. After the addition is complete, continue to maintain the temperature at 62°C with stirring for another 2 hours.
[0109] After the reaction was completed, the reactants were cooled to room temperature, the solid content of the system was measured, and deionized water was added to adjust the solid content to 15.0 ± 0.2 wt%. The actual degree of modification of the acetylacetyl group in the obtained polyvinyl alcohol was determined by ¹H NMR to obtain an aqueous solution of acetylated polyvinyl alcohol.
[0110] Preparation Example 3:
[0111] This preparation example provides a method for preparing an aqueous solution of acetylated polyvinyl alcohol, comprising the following steps:
[0112] Add 85.0 parts by weight of deionized water to the reactor and heat it to 92°C.
[0113] 15.0 parts by weight of polyvinyl alcohol were slowly added under constant stirring, and the mixture was stirred at a constant temperature for 2.5 hours until the polyvinyl alcohol was completely dissolved, thus obtaining an aqueous solution of polyvinyl alcohol.
[0114] Cool the polyvinyl alcohol aqueous solution to 62°C, add 0.075 parts by weight of anhydrous sodium acetate, and stir until homogeneous.
[0115] Maintain the temperature at 62°C and slowly add 2.28 parts by weight of diketene to the system, controlling the dropping rate to complete the process within 1.5 hours. After the addition is complete, continue to maintain the temperature at 62°C with stirring for another 2 hours.
[0116] After the reaction was complete, the reactants were cooled to room temperature, the solid content of the system was measured, and deionized water was added to adjust the solid content to 15.0 ± 0.2 wt%.
[0117] The actual degree of modification of the acetylacetyl group in the obtained polyvinyl alcohol was determined by ¹H NMR, and an aqueous solution of acetylated polyvinyl alcohol was obtained.
[0118] Example 1:
[0119] This embodiment provides an artistic coating with formaldehyde removal and antibacterial functions and its preparation method, including the following steps:
[0120] Step 1: Turn on the cooling water in the reactor jacket and set the circulating water temperature to ensure that the temperature of the material inside the reactor is maintained at 25°C throughout the entire preparation process.
[0121] 15.0 parts by weight of deionized water, 1.5 parts by weight of propylene glycol, 0.2 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether, 0.5 parts by weight of sodium polyacrylate aqueous solution, and 0.1 parts by weight of polyether modified siloxane defoamer were added sequentially to the reactor. The dispersion plate was turned on and stirred at 300 rpm for 10 minutes to form a nonionic surfactant micelle and associative solubilization system in the aqueous phase.
[0122] Then add 1.0 part by weight of activated zinc oxide, increase the speed to 800 rpm, and stir for 10 minutes. Continue stirring slowly by adding 0.5 parts by weight of acetylacetone for 15 minutes.
[0123] Then, 1.0 part by weight of ammonia water was added dropwise, and the pH value of the system was tested and confirmed to be stable at 10.2. The mixture was then kept warm and stirred for 15 minutes to form a uniform complex dispersion.
[0124] Step 2: Maintain the temperature inside the reactor at 25°C, and add 10.0 parts by weight of the acetylated polyvinyl alcohol aqueous solution prepared in Preparation Example 1 to the dispersion solution obtained in Step 1. Increase the stirring speed of the dispersion disc to 1200 rpm and maintain the stirring speed at a constant speed for 20 minutes.
[0125] Step 3: Maintain a high-speed shearing state of 1200 rpm, and sequentially and uniformly add 10.0 parts by weight of rutile titanium dioxide, 15.0 parts by weight of heavy calcium carbonate, and 5.0 parts by weight of talc.
[0126] After continuous high-speed dispersion for 30 minutes, samples were taken and tested using a scraper fineness meter to confirm that the fineness of the slurry was ≤40μm.
[0127] Step 4: Reduce the speed of the dispersing disc to a low-shear state of 300 rpm, and slowly and uniformly add 30.0 parts by weight of anionic styrene-acrylic emulsion. After the addition is complete, maintain the low speed state and stir for 15 minutes to make the system homogeneous.
[0128] Step 5: Add the remaining 0.1 parts by weight of polyether-modified siloxane defoamer and 0.3 parts by weight of hydrophobic-modified polyurethane associative thickener to the reactor, maintain stirring at 300 rpm for 10 minutes, let stand to defoam, filter through a 100-mesh filter bag, weigh and package to obtain the target coating.
[0129] Example 2:
[0130] This embodiment provides an artistic coating with formaldehyde removal and antibacterial functions and its preparation method, including the following steps:
[0131] Step 1: Turn on the cooling water in the reactor jacket and set the circulating water temperature to ensure that the temperature of the material inside the reactor is maintained at 30°C throughout the entire preparation process.
[0132] 20.0 parts by weight of deionized water, 2.2 parts by weight of propylene glycol, 0.4 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether, 0.7 parts by weight of sodium polyacrylate aqueous solution and 0.2 parts by weight of polyether modified siloxane defoamer were added sequentially to the reactor. The dispersion plate was turned on and stirred at 350 rpm for 10 minutes to form micelles and associated solubilization structures in the aqueous phase.
[0133] Then add 2.0 parts by weight of active zinc oxide, increase the speed to 900 rpm, and stir for 10 minutes.
[0134] Slowly add 1.0 part by weight of acetylacetone while maintaining the stirring speed, and keep stirring for 15 minutes;
[0135] Then, 1.7 parts by weight of ammonia water were added dropwise, and the pH value of the system was tested and confirmed to be stable at 10.4. The mixture was then kept warm and stirred for 15 minutes to form a uniform complex dispersion.
[0136] Step 2: Keep the temperature inside the vessel at 30°C, and add 12.5 parts by weight of the acetylated polyvinyl alcohol aqueous solution prepared in Preparation Example 2 to the dispersion solution obtained in Step 1.
[0137] Increase the speed of the dispersing disc to 1350 rpm and maintain a constant speed for 20 minutes.
[0138] Step 3: Maintain a high-speed shearing state of 1350 rpm, and sequentially and uniformly add 12.5 parts by weight of rutile titanium dioxide, 17.5 parts by weight of heavy calcium carbonate, and 7.5 parts by weight of talc.
[0139] After continuous high-speed dispersion for 35 minutes, samples were taken and tested using a scraper fineness meter to confirm that the fineness of the slurry was ≤40μm.
[0140] Step 4: Reduce the speed of the dispersing disc to a low-shear state of 350 rpm, and slowly and uniformly add 35.0 parts by weight of anionic styrene-acrylic emulsion. After the addition is complete, maintain the low speed state and stir for 15 minutes to make the system homogeneous.
[0141] Step 5: Add the remaining 0.2 parts by weight of polyether-modified siloxane defoamer and 0.5 parts by weight of hydrophobic-modified polyurethane associative thickener to the reactor, maintain stirring at 350 rpm for 10 minutes, let stand to defoam, filter through a 100-mesh filter bag, weigh and package to obtain the target coating.
[0142] Example 3:
[0143] This embodiment provides an artistic coating with formaldehyde removal and antibacterial functions and its preparation method, including the following steps:
[0144] Step 1: Turn on the cooling water in the reactor jacket and set the circulating water temperature to ensure that the temperature of the material inside the reactor is maintained at 35°C throughout the entire preparation process.
[0145] 25.0 parts by weight of deionized water, 3.0 parts by weight of propylene glycol, 0.6 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether, 1.0 parts by weight of sodium polyacrylate aqueous solution and 0.25 parts by weight of polyether modified siloxane defoamer were added sequentially to the reactor. The dispersion plate was turned on and stirred at 400 rpm for 10 minutes to form micelles and associated solubilization structures in the aqueous phase.
[0146] Then add 3.0 parts by weight of active zinc oxide, increase the speed to 1000 rpm, and stir for 10 minutes.
[0147] Slowly add 1.5 parts by weight of acetylacetone while maintaining the stirring speed, and keep stirring for 15 minutes;
[0148] Then, 2.5 parts by weight of ammonia water were added dropwise, and the pH value of the system was tested and confirmed to be stable at 10.5. The mixture was then kept warm and stirred for 15 minutes to form a uniform complex dispersion.
[0149] Step 2: Maintain the temperature inside the reactor at 35°C, and add 15.0 parts by weight of the acetylated polyvinyl alcohol aqueous solution prepared in Preparation Example 3 to the dispersion solution obtained in Step 1. Increase the stirring speed of the dispersion disc to 1500 rpm and maintain the stirring speed at a constant speed for 20 minutes.
[0150] Step 3: Maintain a high-speed shearing state of 1500 rpm, and sequentially and uniformly add 15.0 parts by weight of rutile titanium dioxide, 20.0 parts by weight of heavy calcium carbonate, and 10.0 parts by weight of talc.
[0151] After continuous high-speed dispersion for 40 minutes, samples were taken and tested using a scraper fineness meter to confirm that the fineness of the slurry was ≤40μm.
[0152] Step 4: Reduce the speed of the dispersion disc to a low-shear state of 400 rpm, and slowly and uniformly add 40.0 parts by weight of anionic styrene-acrylic emulsion. After the addition is complete, maintain the low speed state and stir for 15 minutes to make the system homogeneous.
[0153] Step 5: Add the remaining 0.25 parts by weight of polyether-modified siloxane defoamer and 0.8 parts by weight of hydrophobic-modified polyurethane associative thickener to the reactor, maintain stirring at 400 rpm for 10 minutes, let stand to defoam, filter through a 100-mesh filter bag, weigh and package to obtain the target coating.
[0154] Example 4:
[0155] This embodiment provides an artistic coating with formaldehyde removal and antibacterial functions and its preparation method, including the following steps:
[0156] The proportions of each raw material group and the preparation temperature in this embodiment are exactly the same as in Example 2. The only difference is that the process robustness is examined under more stringent process times.
[0157] The operation of steps 1 to 3 is the same as in Example 2, but in step 3, the high-speed dispersion time (1350 rpm) after adding pigments and fillers is extended from 35 minutes to 60 minutes to simulate the delay in the high-speed dispersion process that may occur in large-scale industrial production.
[0158] The additional mechanical heat generated by prolonged high shear is forcibly removed by the jacket cooling water, ensuring that the temperature is always maintained at 30°C.
[0159] Sampling and testing fineness ≤40μm.
[0160] Steps 4 and 5 are performed in the same manner as in Example 2. After standing and defoaming, the product is filtered through a 100-mesh filter bag, weighed, and packaged to obtain the target coating.
[0161] Throughout the entire production process, no back-coarsening or demulsification occurred in the system under prolonged high shear.
[0162] Comparative Example 1:
[0163] Compared with Example 2, the difference is that acetylacetone is not added to the formula, and the weight of the missing part is made up by deionized water, while the rest are the same.
[0164] Comparative Example 2:
[0165] Compared with Example 2, the difference lies in the change of process sequence. A one-pot mixing method is adopted, in which water, propylene glycol, isotridecyl alcohol polyoxyethylene ether, sodium polyacrylate aqueous solution, polyether modified siloxane defoamer, active zinc oxide, acetylacetone, ammonia, acetylated polyvinyl alcohol aqueous solution, pigments and fillers, anionic styrene-acrylic emulsion, and hydrophobic modified polyurethane associative thickener are added to the reactor simultaneously without separate steps. The material temperature is controlled at 30°C. The mixture is first stirred at 350 rpm for 10 minutes, then stirred at 900 rpm for 40 minutes, then dispersed at 1350 rpm for 55 minutes, and finally stirred at 350 rpm for 25 minutes. After standing to defoam, it is filtered through a 100-mesh filter bag.
[0166] Comparative Example 3:
[0167] Compared with Example 2, the difference is that propylene glycol and isotridecyl alcohol polyoxyethylene ether are not added to the formulation, and the weight of the corresponding missing parts is made up by deionized water, while the rest are the same.
[0168] Comparative Example 4:
[0169] Compared with Example 2, the difference is that an equal weight of conventional polyvinyl alcohol aqueous solution (unmodified, degree of alcoholysis 88 mol%, degree of polymerization 1700, solid content 15 wt%) was used instead of acetylated polyvinyl alcohol aqueous solution, all other aspects are the same.
[0170] Comparative Example 5:
[0171] Compared with Example 2, the difference is that the cooling water in the reactor jacket is not turned on during the preparation process, and the material inside the reactor is allowed to heat up naturally due to high-speed dispersion (measured to 55°C). All other aspects are the same.
[0172] Experimental description for Test Example 1:
[0173] 1. Take the base liquid from step 1 of Example 2 as the experimental subject, and denote the base liquid as test sample A.
[0174] The bottom liquid obtained at the same process time point as Example 2 in Comparative Example 3 was used as a comparison object and denoted as Test Sample B.
[0175] Take 5 mL of test sample, add 95 mL of deionized water, and use an ultrasonic cleaner at a frequency of 40 kHz to ultrasonically disperse for 5 minutes at room temperature to prepare the test dilution.
[0176] 2. Transfer the diluted solution to be tested to a test cuvette equipped with a temperature control system, let it stand for 3 minutes to eliminate air bubbles, and ensure that the sample cell temperature is stable at 25.0±0.1℃.
[0177] 3. The test was conducted using a dynamic light scattering instrument. The laser wavelength was set to 633 nm and the scattering angle to 90°. The autocorrelation function attenuation data of the scattered light intensity was collected using the instrument's photon correlation spectroscopy software.
[0178] 4. Each sample was subjected to three consecutive scans, each scan lasting 60 seconds. The average of the three test results was taken to obtain the particle size distribution data.
[0179] The autocorrelation function is fitted using the CONTIN algorithm to output the distribution curve of the hydrodynamic diameter and the polydispersity coefficient parameter.
[0180] Table 1. Particle size distribution parameters of test sample A and test sample B
[0181]
[0182] It should be noted that the Z-average particle size in Table 1 is the hydrodynamic particle size of the liquid phase scatterer obtained by dynamic light scattering method after the test sample has been diluted and ultrasonically treated.
[0183] The D50 of the raw material active zinc oxide is a powder particle size parameter. Since the test objects, sample states and test principles of the two are different, they cannot be directly compared numerically.
[0184] Based on the data in Table 1, combined with Figure 1 The distribution curves shown indicate that, in the early stages of the in-situ complexation reaction, the systems of the examples and the comparative examples exhibited differences in their micro-aggregation states.
[0185] The Z-average particle size of test sample A is small, and the polydispersity index remains at a low level, with its distribution curve showing a single narrow peak.
[0186] This reflects that in the mixed solvent environment constructed by propylene glycol and nonionic wetting agents, zinc-containing species in the system exhibit a lower degree of aggregation and a narrower particle size distribution, which is consistent with the inhibitory effect of the mixed dispersion and solubilization environment formed by propylene glycol and nonionic surfactants on particle aggregation.
[0187] In contrast, the Z-average particle size of test sample B was significantly increased, and the polydispersity index was elevated. The distribution curve showed obvious broadening and multi-peak distribution characteristics, with large particle volume fraction dominating.
[0188] Due to the lack of mixed dispersion and solubilization effects provided by propylene glycol and nonionic surfactants in the system, zinc-containing species in the system are more prone to aggregation, causing the particle size distribution to shift significantly towards larger sizes and forming a wider polydisperse system.
[0189] The above test results support, on a physicochemical scale, the role of the mixed dispersion and solubilization system formed by propylene glycol and nonionic surfactant in reducing the aggregation of zinc-containing species and maintaining the dispersion stability of the early complexing substrate, which constitutes the technical basis for this solution to suppress microscopic defects in the paint film.
[0190] Experimental description for Test Example 2:
[0191] 1. The coating prepared in Example 2 was used as the experimental subject. The coating was uniformly coated on the ZnSeATR crystal test surface of the Fourier transform infrared spectrometer, and the wet film thickness was controlled to be about 100 μm to prepare an in-situ sample for infrared spectroscopy testing.
[0192] 2. Place the ZnSeATR crystal coated with a wet film in the attenuated total reflectance in-situ test state of the Fourier transform infrared spectrometer, and set the test environment temperature to 25℃ and the relative humidity to 50%.
[0193] 3. Turn on the instrument to perform continuous dynamic scanning, and set the spectral resolution to [value missing]. The scanning range is 4000-400. .
[0194] The moment when the sample coating is completed and placed into the instrument is recorded as 0 minutes. Infrared spectra are then collected at 30 minutes, 60 minutes, 120 minutes and 240 minutes.
[0195] 4. Extract spectral data from the characteristic absorption regions of acetyl-acetyl carbonyl and ammonia-related characteristic absorption regions, analyze the peak position changes of the carbonyl stretching vibration absorption peak and the attenuation of the integral intensity of the ammonia-related characteristic peak, and perform baseline correction and normalization on the spectral curves at different time points.
[0196] The relative retention rate of the ammonia characteristic peak was calculated by normalizing the integral intensity of the corresponding characteristic peak in the original coating sample before coating to 100%.
[0197] Table 2. Dynamic evolution parameters of characteristic infrared absorption peaks during the coating drying process in Example 2.
[0198]
[0199] Based on the data in Table 2, combined with Figure 2 The spectral evolution process reveals that in the initial stage of coating drying (0 minutes), the acetylacetyl groups on the acetylated polyvinyl alcohol side chains mainly exist in a free, uncoordinated form, with their typical carbonyl stretching vibration absorption peak located at 1718.4. .
[0200] As the film-forming process continued, the relative retention rate of the ammonia characteristic peak in the system decreased significantly, reaching only 3.4% at 240 minutes, indicating that the volatile ammonia-containing components in the system were gradually lost from the coating body during the film-forming process.
[0201] As the volatile ammonia-containing components gradually decrease, the carbonyl group of the acetyl group undergoes a continuous red shift, from 1718.4... Gradually move to 1634.1 .
[0202] The shift of the absorption peak toward lower wavenumbers indicates a significant change in the electronic environment of the acetoacetyl carbonyl group. This change is consistent with the characteristic of a decrease in the carbonyl bond force constant after the acetoacetyl group participates in the coordination of zinc species, supporting the formation of polymer-zinc coordination during the coating drying process.
[0203] The test results show that as the volatilization process progresses, the acetylacetyl-related carbonyl peak and the ammonia-related characteristic peak change synchronously, indicating that the coordination environment of zinc species in the system changes with the drying process and gradually forms coordination crosslinking with acetylated polyvinyl alcohol.
[0204] This process supports the time correlation between internal coordination crosslinking of the coating film and the gradual loss of volatile components, exhibiting the characteristics of delayed crosslinking. This is beneficial for reducing abnormal thickening of the coating in the liquid phase caused by premature interaction between active zinc species and emulsion groups.
[0205] Experimental description for Test Example 3:
[0206] 1. The coatings prepared in Example 2 and Comparative Example 1 were used as experimental subjects.
[0207] Take 2 mL of test sample and place it on the test platform of the rotational rheometer. Use a parallel plate clamp with a diameter of 40 mm and set the test gap to 1 mm.
[0208] 2. Apply an appropriate amount of low-viscosity dimethyl silicone oil to the exposed surface of the sample at the outer edge of the parallel plate to reduce the interference of irregular evaporation of moisture at the edge during the test on the experimental results. Set and keep the temperature of the sample stage at 25.0±0.1℃ and let it stand for 2 minutes to allow the sample to eliminate stress history.
[0209] 3. The test was conducted using a time-scan mode with small amplitude oscillation shearing.
[0210] The oscillation frequency was set to 1 Hz, and the strain amplitude was kept constant at 1%. Pre-testing confirmed that the strain parameter was within the linear viscoelastic region of the sample.
[0211] 4. Start the program to perform continuous rheological scanning, and set the total test duration to 120 minutes.
[0212] The instrument data acquisition software records the values of storage modulus (G') and loss modulus (G'') over time in real time, extracts data at different time points, and determines the rheological gel point time when the storage modulus and loss modulus values are equal.
[0213] Table 3. Evolution of storage modulus and loss modulus of coatings in Example 2 and Comparative Example 1 over time.
[0214]
[0215] Based on the data in Table 3, combined with Figure 3 The evolution trend of the rheological curves shows a significant difference between Example 2 and Comparative Example 1 in the development of viscoelasticity over time.
[0216] For Example 2, during the initial and early stages of the test (0-45 minutes), the loss modulus (G'') of the system was always greater than the storage modulus (G'), and the coating as a whole exhibited typical fluid viscosity characteristics. This state is beneficial for the spreading and leveling of the coating during the construction process.
[0217] As time progresses, around 54 minutes, the storage modulus curve intersects with the loss modulus curve (i.e., the rheological gel point), after which the storage modulus becomes dominant, indicating that a continuous network structure that can penetrate the system gradually forms inside the system, and the elastic response begins to dominate.
[0218] This evolution process reflects that the proposed scheme uses acetylacetone and ammonia to coordinate and passivate the active zinc-containing species in the system, providing sufficient buffer time in the early stage of film formation, so that Example 2 still exhibits obvious delayed structure building behavior under limited volatilization conditions; combined with the synchronous changes of volatile components and carbonyl characteristic peaks with drying time in Test Example 2, it supports the existence of a delayed crosslinking process in the actual film formation process that is related to volatilization and coordination crosslinking.
[0219] In contrast, data from Comparative Example 1 (without acetylacetone) showed that at the initial 0-minute mark of the test, its storage modulus (451.2 Pa) was significantly higher than its loss modulus (115.6 Pa), indicating that the system already exhibited strong solid-like elastic characteristics.
[0220] This indicates that, due to the lack of chelating coordination provided by acetylacetone, strong ion association or cross-linking occurs between the active zinc-containing species in the system and the anionic carboxyl groups in the base emulsion during the coating preparation or storage stage.
[0221] This premature gelation causes the coating to lose its workable liquid phase state and prevents the release of internal shrinkage stress through leveling during film formation.
[0222] The above rheological test results support the role of the dual-ligand coordination system in controlling the rate of heterogeneous crosslinking reaction and maintaining the fluidity of the system in the early stage, from the perspective of macromolecular motion.
[0223] Experimental description for Test Example 4:
[0224] 1. The coatings prepared in Examples 1 to 4, as well as Comparative Examples 1, 2 and 5, were used as experimental subjects.
[0225] In a constant temperature chamber of 25.0±0.2℃, the initial viscosity of each sample was tested using a Stormer viscometer, and the viscosity readings (unit: KU) were recorded. The initial macroscopic state of the coating after preparation was also recorded.
[0226] 2. Place each paint sample into a 0.5L standard tinplate paint container and seal the lid to prevent moisture evaporation. Transfer the sealed paint containers into an electric thermostatic drying oven set at 50±1℃ for accelerated storage testing.
[0227] 3. After continuous heat storage for 30 days, remove the paint can from the constant temperature chamber and place it in a room temperature environment of 25°C for 24 hours to allow the internal temperature of the sample to equalize to room temperature.
[0228] 4. Open the paint can and observe the macroscopic state of the sample. Record whether there is any layering, flocculation, demulsification, or gel clumping within the system.
[0229] The sample was stirred at low speed using a paint mixing knife. For samples that remained in a fluid state, the viscosity after heat storage was tested again using a Stormer viscometer, and the difference in viscosity change was calculated. ).
[0230] For samples that have undergone severe gelation or clumping that exceeds the instrument's measurement range, stop the measurement and record it as gel.
[0231] Table 4. Storage stability test data of the coatings in the examples and comparative examples.
[0232]
[0233] According to Table 4 and Figure 4 Based on the data and macroscopic phenomena observed during the coating preparation process, the various formulation systems exhibited systematic differences in resistance to anionic emulsion demulsification and storage stability.
[0234] Examples 1 to 4 all exhibited a homogeneous fluid state after preparation, with initial viscosity controlled within the workable range of 94 to 102 KU;
[0235] After being subjected to accelerated heat storage at 50℃ for 30 days, its viscosity increased ( All values remained below 5 KU, with no sedimentation, stratification, or obvious abnormal thickening.
[0236] Example 4 maintained a stable viscosity evolution even after extending the high-shear dispersion time, reflecting the process robustness of the system under harsh mechanical forces.
[0237] These results support the following mechanism: propylene glycol forms a mixed dispersion and solubilization environment with nonionic surfactants, while acetylacetone and ammonia coordinate with the active zinc-containing species in the system, thereby jointly reducing the possibility of premature interaction between zinc-containing species and emulsion carboxyl groups.
[0238] This mechanism reduces the likelihood of premature contact and coordination between active zinc-containing species in the system and carboxyl groups in anionic styrene-acrylic emulsions, thereby inhibiting unplanned crosslinking during production and storage.
[0239] In the comparative test, Comparative Example 1 did not add acetylacetone, and lacked the chelating coordination effect provided by acetylacetone. The system's ability to coordinate and passivate active zinc-containing species was reduced, making it easier for zinc-containing species to interact with carboxyl groups in the emulsion, resulting in severe flocculation of the coating during the paint mixing stage.
[0240] Comparative Example 2 used a one-pot mixing method, skipping the pre-construction steps of dispersing and solubilizing structures and complexing dispersion base liquids. This caused the active zinc-containing species to come into contact with the emulsion before they had fully established coordination stabilization, resulting in severe demulsification and loss of normal processing performance of the system.
[0241] In Comparative Example 5, no cooling or temperature control was applied during the preparation process. Mechanical shear heat caused the system temperature to rise, which may weaken the stability of the dispersed solubilized structure in the system and may accelerate the loss of volatile coordinating components.
[0242] Its initial viscosity increased to 115.3 KU, exhibiting a certain degree of pre-crosslinking;
[0243] During subsequent thermal storage, the original coordination stabilizing effect of the system is further weakened, and with the continuous increase in the degree of structuring, it eventually manifests as severe gel agglomeration.
[0244] The test data above indicate from a macroscopic rheological perspective that the specific order of component addition and temperature control process are beneficial to maintaining the liquid-phase stability of this zinc-containing coordination crosslinking coating.
[0245] Experimental description for Test Example 5:
[0246] 1. The coatings prepared in Examples 1 to 4, as well as Comparative Examples 3 and 4, were used as experimental subjects.
[0247] Since Comparative Example 1 and Comparative Example 2 had severe flocculation or demulsification during the preparation stage, and could not obtain homogeneous fluid samples that meet the requirements for normal coating application, they were not included in this test scope.
[0248] 2. Preparation of test samples for crack resistance and smoothness. A wet film with a thickness gradient of 0 to 5 mm was prepared on a standard asbestos-free fiber cement board using a wedge coater. A separate standard glass plate was prepared with a wet film of uniform thickness using a 150 μm wire rod coater.
[0249] The coated sample was placed horizontally in a constant temperature and humidity chamber with a temperature of 25±1℃ and a relative humidity of 50±5% for continuous drying and curing for 7 days.
[0250] 3. Test the maximum crack-resistant thickness and surface roughness. After the gradient thickness sample is completely dry, use a reading microscope to observe the coating surface along the thickness increase direction, and record the maximum initial nominal wet film thickness corresponding to the location where no cracks were observed, accurate to 0.1 mm, and take this as the maximum crack-resistant thickness.
[0251] A stylus-type surface roughness meter was used to perform line scanning on the dry film on the glass plate. The scanning length was set to 10 mm, and the arithmetic mean roughness (Ra) value was extracted to characterize the surface smoothness.
[0252] 4. Test the washability.
[0253] A wet film was prepared on asbestos-free fiber cement board using a 120 μm wire bar coater and cured for 14 days under standard conditions.
[0254] The sample was fixed on the scrub resistance tester. A standard boar bristle brush and a 0.5% (w / w) detergent solution were used as the scrubbing medium, and the scrubbing frequency was set to 37 times / minute. The number of scrubbing cycles before the coating was brushed through and the substrate was exposed was recorded.
[0255] Table 5. Physical and mechanical properties and appearance smoothness test data of the coatings in the examples and comparative examples.
[0256]
[0257] According to Table 5 and Figure 5 Based on the data and the differences in formulations of each system, it can be observed that micro-components and reaction processes have a direct impact on the macro-physical properties of the coating.
[0258] The maximum crack-resistant coating thickness of Examples 1 to 4 all exceeded 3.0 mm, the surface roughness was maintained at around 1.1 μm, and the number of washes reached more than 4000.
[0259] This reflects that during the drying and film-forming process, as moisture and ammonia evaporate, the acetyl groups on the macromolecular chains undergo delayed coordination crosslinking with zinc-containing species, gradually constructing a polymer-metal coordination crosslinking network that runs through the coating film.
[0260] During the phase transition from liquid to solid, this network provides a time window for stress relaxation of the capillary tension generated by volume shrinkage inside the coating, thereby improving the crack resistance under thick coating application.
[0261] Meanwhile, the formation of the cross-linked network significantly enhances the cohesive strength and water resistance of the coating, giving it a longer service life under mechanical washing.
[0262] In Comparative Example 3, the surface roughness increased sharply to 8.45 μm in the absence of the mixed dispersion and solubilization effects provided by propylene glycol and nonionic surfactants.
[0263] This may be related to the fact that zinc-containing species in the system are not sufficiently dispersed, aggregate or precipitate in the aqueous phase, and form large micro-uniform regions during film formation, resulting in decreased smoothness and the generation of mechanical defect regions, which indirectly reduces crack resistance and washability.
[0264] Comparative Example 4 used unmodified conventional polyvinyl alcohol, which maintained normal surface smoothness, but its maximum crack-resistant thickness was only 1.8 mm, and the number of washes was significantly reduced to 1850.
[0265] Unmodified polyvinyl alcohol segments lack acetyl groups for coordination, making it difficult to form an effective coordination crosslinking network through the aforementioned zinc-containing species. They mainly rely on hydrogen bonding and physical entanglement of segments to maintain their structure.
[0266] When moisture evaporation causes the coating to shrink drastically, this physical entanglement cannot effectively disperse stress, leading to cracking of the thick coating.
[0267] Furthermore, the water-soluble linear polyvinyl alcohol chains are prone to swelling and loss during scrub resistance tests, weakening the overall mechanical structure of the coating film.
[0268] The test results support the role of the specific acetylacetyl modified structure and the corresponding coordination crosslinking network in improving the overall mechanical properties of the coating.
[0269] Experimental description for Test Example 6:
[0270] 1. The coatings prepared in Examples 1 to 4 and Comparative Example 4 were used as experimental subjects.
[0271] A coating was prepared on a standard glass plate using a 150μm wire bar coater and cured for 14 days in a constant temperature and humidity environment of 25±1℃ and 50±5% to produce an initial test sample.
[0272] 2. The formaldehyde removal performance of the coating was tested using a 1m³ environmental test chamber method. The sample was placed in the center of the test chamber, sealed, and a specified amount of formaldehyde gas was injected into the chamber to achieve an initial concentration of 1.0 mg / m³.
[0273] Turn on the cabin circulation fan and run it for 24 hours in the dark. Extract the gas in the cabin to measure the residual formaldehyde concentration and calculate the initial formaldehyde purification efficiency.
[0274] 3. Based on the coating antibacterial performance test standard, the antibacterial rate of Escherichia coli (ATCC25922) was determined by the film application method.
[0275] A concentration of 10 was added to the sample surface. 5 -10 6The bacterial culture of CFU / mL was covered with a polyethylene film and then incubated in an incubator at 37°C and relative humidity greater than 90% for 24 hours.
[0276] The bacterial solution on the sample surface and film was washed off, viable bacteria were counted, and the initial antibacterial rate was calculated.
[0277] 4. Fix the remaining samples prepared in the same batch onto the scrub resistance tester, and use deionized water as the medium to perform 500 and 1000 consecutive scrubbing cycles respectively.
[0278] After washing, the samples were air-dried at room temperature. Steps 2 and 3 were repeated to measure the formaldehyde purification efficiency and antibacterial rate of each sample at different washing and aging stages.
[0279] Table 6. Data on the degradation of formaldehyde removal and antibacterial function of the coatings in the examples and comparative examples during the water washing and aging process.
[0280]
[0281] According to Table 6 and Figure 6 The data shows that the coordination crosslinking network structure in the coating has a significant impact on the long-term functional retention performance of the coating.
[0282] After 1000 mechanical water washes, the formaldehyde purification rate of Examples 1 to 4 remained within 10%, and the antibacterial rate remained above 93%.
[0283] This indicates that the acetoacetyl groups introduced into the acetoacetyl polyvinyl alcohol segments can participate in the coordination of zinc-containing species during film formation, thereby forming a polymer-metal coordination crosslinking structure.
[0284] This cross-linking network provides coordination and cross-linking anchoring for polyvinyl alcohol segments, limiting the free migration and dissolution of water-soluble polymer segments when water penetrates.
[0285] On the other hand, the coordination crosslinking network helps limit the migration and loss of zinc-containing components during the washing process, thereby helping to maintain the long-term formaldehyde removal and antibacterial properties of the coating.
[0286] The test data of Comparative Example 4 showed that although its initial formaldehyde removal and antibacterial functions reached certain indicators, after 500 and 1000 water washes, both functional indicators showed a sharp decline. After 1000 washes, the formaldehyde purification rate was only 31.5%, and the antibacterial rate dropped to 39.8%.
[0287] Since Comparative Example 4 uses ordinary polyvinyl alcohol without side chain modification, its chain segments lack acetyl-acetyl coordination sites, making it difficult to form the above-mentioned polymer-zinc species coordination crosslinking structure.
[0288] In the coating, the unmodified polyvinyl alcohol exists mainly through physical blending, hydrogen bonding, and chain segment entanglement, lacking the aforementioned coordination crosslinking anchoring effect.
[0289] When the sample is washed and soaked in water, the uncrosslinked water-soluble polyvinyl alcohol swells and diffuses out into the external aqueous phase, thereby reducing the retention capacity of the coating structure and related functional components during the washing process.
[0290] Meanwhile, due to the lack of an effective coordination cross-linking anchoring structure, the migration and loss of zinc-containing components increase during repeated washing, resulting in a significant decrease in antibacterial properties.
[0291] These experimental data support the role of constructing a coordination crosslinking anchoring structure by acetylated polyvinyl alcohol in improving the long-term functional retention of coatings.
[0292] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An artistic paint with formaldehyde removal and antibacterial functions, characterized in that, The artistic paint is made from raw materials comprising the following parts by weight: Deionized water: 15.0–25.0 parts; Propylene glycol: 1.5–3.0 parts; Isomeric tridecyl alcohol polyoxyethylene ether: 0.2–0.6 parts; Sodium polyacrylate aqueous solution: 0.5–1.0 parts; Active zinc oxide: 1.0–3.0 parts; Acetylacetone: 0.5–1.5 parts; Ammonia solution: 1.0–2.5 parts; Aqueous acetylated polyvinyl alcohol aqueous solution: 10.0–15.0 parts; Pigments and fillers: 30.0–45.0 parts; Anionic styrene-acrylic emulsion: 30.0–40.0 parts; Polyether-modified siloxane defoamer: 0.2–0.5 parts; Hydrophobic modified polyurethane associative thickener: 0.3-0.8 parts.
2. The formaldehyde-removing and antibacterial artistic paint according to claim 1, characterized in that, The pigments and fillers are composed of rutile titanium dioxide, heavy calcium carbonate and talc, and the weight ratio of rutile titanium dioxide, heavy calcium carbonate and talc is (10.0~15.0):(15.0~20.0):(5.0~10.0).
3. The formaldehyde-removing and antibacterial artistic coating according to claim 1, characterized in that, The average number of ethylene oxide additions to the isomeric tridecyl alcohol polyoxyethylene ether is 6; The active zinc oxide is a powder with a purity of ≥99.7wt% and an average particle size D50 of 0.8μm; The anionic styrene-acrylic emulsion is a high-molecular-weight aqueous dispersion copolymerized from styrene, butyl acrylate and carboxyl-containing unsaturated monomers, with a solid content of 48 wt% and a pH value of 7.5–8.
0.
4. The formaldehyde-removing and antibacterial artistic coating according to claim 1, characterized in that, The acetylated polyvinyl alcohol aqueous solution has a solid content of 15.0 ± 0.2 wt%, and is prepared from raw materials comprising the following parts by weight: Deionized water: 85.0 parts; Partially hydrolyzed polyvinyl alcohol: 15.0 parts; Anhydrous sodium acetate: 0.075 parts; Diketene: 1.14–2.28 parts.
5. The formaldehyde-removing and antibacterial artistic coating according to claim 4, characterized in that, The method for preparing the acetylated polyvinyl alcohol aqueous solution includes the following steps: Heat deionized water to 92°C, add a portion of alcoholysis-type polyvinyl alcohol while stirring at a constant speed, and stir at a constant temperature until completely dissolved. Cool to 62℃, add anhydrous sodium acetate and stir until well mixed; Maintain the temperature at 62℃ and add diketene dropwise, controlling the dropwise addition process to be completed within 1 to 1.5 hours. After the dropwise addition is completed, continue to keep the temperature at 62℃ and stir the reaction for 2 hours. After the reaction was completed, the mixture was cooled to room temperature, and deionized water was added to adjust the solid content to 15.0 ± 0.2 wt%.
6. A method for preparing an art paint with formaldehyde removal and antibacterial function, comprising the art paint with formaldehyde removal and antibacterial function according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Control the temperature of the material in the reactor to 25-35℃, and add deionized water, propylene glycol, isotridecyl alcohol polyoxyethylene ether, sodium polyacrylate aqueous solution and the first part of polyether modified siloxane defoamer in sequence and stir. Then, active zinc oxide was added and stirred to disperse the mixture. Acetylacetone was added dropwise while maintaining the stirring speed, followed by the addition of ammonia water. The pH of the system was controlled between 10.2 and 10.5 to form a dispersion base liquid. S2. Maintain the temperature inside the reactor, add an acetylated polyvinyl alcohol aqueous solution to the dispersion base liquid, and increase the rotation speed to maintain a constant stirring speed; S3. Maintain high-speed shearing, add pigments and fillers sequentially, continue high-speed dispersion, and control the slurry fineness to ≤40μm; S4. Reduce the rotation speed and slowly and uniformly add the anionic styrene-acrylic emulsion. After the addition is complete, maintain low-speed stirring. S5. Add the second part of polyether-modified siloxane defoamer and hydrophobic-modified polyurethane associative thickener, stir at low speed, let stand to defoam, and then filter to obtain the final product.
7. The method for preparing an artistic coating with formaldehyde removal and antibacterial function according to claim 6, characterized in that, In step S1, deionized water, propylene glycol, isotridecyl alcohol polyoxyethylene ether, sodium polyacrylate aqueous solution and the first part of polyether modified siloxane defoamer are added in sequence, and then stirred at a speed of 300-400 rpm for 10 minutes. After adding the active zinc oxide, increase the speed to 800-1000 rpm and stir for 10 minutes.
8. The method for preparing an art paint with formaldehyde removal and antibacterial function according to claim 6, characterized in that, In step S3, the rotation speed during high-speed shearing is 1200-1500 rpm, and the high-speed dispersion time is 30-60 minutes. During high-speed dispersion, the temperature is maintained at 25-35℃ by controlling the cooling water in the reactor jacket.
9. The method for preparing an artistic coating with formaldehyde removal and antibacterial function according to claim 6, characterized in that, In step S4, the speed after reducing the speed is 300-400 rpm; in step S5, the speed of low-speed stirring is 300-400 rpm, and the stirring time is 10 minutes.
10. The method for preparing an artistic coating with formaldehyde removal and antibacterial function according to claim 10, characterized in that, The weight ratio of the first part of the polyether-modified siloxane defoamer to the second part of the polyether-modified siloxane defoamer is 1:1.
